End of induction positron emission tomography complete response (PET‐CR) as a surrogate for progression‐free survival in previously untreated follicular lymphoma. (2nd May 2022) - Dixon, Jesse G.; Dimier, Natalie; Nielsen, Tina; Zheng, Jamie; Marcus, Robert; Morschhauser, Franck; Evens, Andrew M.; Federico, Massimo; Blum, Kristie A.; Shi, Qian
Summary: Progression‐free survival (PFS) has been the regulatory primary end‐point for recent phase III trials in first‐line follicular lymphoma (FL), but requires prolonged follow‐up. Complete response (CR) at 30 months after initiation of induction treatment was validated as surrogate end‐point for PFS. Our objective was to further evaluate surrogacy of CR measured by [ 18 F] fluorodeoxyglucose (FDG) positron emission tomography (PET) imaging at the end of induction (EoI). Individual patient data were analysed from 1505 patients from five randomized trials. Trial‐level surrogacy examining the association between treatment effects on EoI‐PET‐CR and PFS was evaluated using linear regression ( R WLS 2 ) and bivariate Copula ( R Copula 2 ) models. Although EoI‐PET‐CR strongly predicted PFS at a prognostic level, the trial‐level assessment did not show strong correlation ( R WLS 2 = 0.56, confidence interval [CI]: 0.20–0.88; R Copula 2 = 0.35, CI: 0.0–0.82). The high uncertainty in estimation was possibly due to the small number of trials and the population of patients with available PET data. Maintenance therapy affecting PFS beyond induction treatment, but not EoI‐PET‐CR end‐point, may have distorted the association between treatment effects. However, there will probably be a number of additional trials approaching completion with available PET response data. Refined evaluation of PET‐CR based surrogate end‐points is still warranted.